Reduction of the secretory response to Escherichia coli heat-stable enterotoxin by thiol and disulfide compounds. - Greenberg, R N (1983)
We examined the effects of disulfide and thiol compounds on Escherichia coli heat-stable enterotoxin (ST) and cyclic GMP-induced secretion. Both cystamine and cystine (disulfide compounds) reduced the secretory responses to submaximal doses of ST in suckling mice (at 0.5 mumol per mouse) and reduced ST activation of guanylate cyclase (by 33 to 73% at 1 mM). In higher doses, cystamine completely eradicated a maximally effective ST dose as well. In addition, the sulfhydryl (thiol) compounds cysteamine, cysteine, and acetylcysteine strikingly reduced the secretory response and the guanylate cyclase response to ST. Neither the disulfide nor the thiol compounds tested reduced cyclic GMP-induced secretion. These studies suggest that disulfide and thiol compounds both block ST-induced secretion before its activation of guanylate cyclase. Taken with the work of others, these findings suggest that disulfide compounds may alter the oxidation reduction state of a cell or act directly on the guanylate cyclase enzyme, whereas thiol compounds may inactivate ST itself by breaking its disulfide bridges, or it may alter guanylate cyclase activation by ST. Both families of compounds deserve further consideration among potential antisecretory agents for application in the control of ST-induced diarrhea.